2010
DOI: 10.1007/s00280-009-1234-z
|View full text |Cite
|
Sign up to set email alerts
|

Voreloxin, a first-in-class anticancer quinolone derivative, acts synergistically with cytarabine in vitro and induces bone marrow aplasia in vivo

Abstract: Main purposeVoreloxin is a first-in-class anticancer quinolone derivative that intercalates DNA and inhibits topoisomerase II, inducing site-selective DNA damage. Voreloxin is in clinical studies, as a single agent and in combination with cytarabine, for the treatment of acute myeloid leukemia (AML). The preclinical studies reported here were performed to investigate the activity of voreloxin alone and in combination with cytarabine, in support of the clinical program.Research questionsIs single agent voreloxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…Arsenic trioxide combined with LDAC in elderly patients with AML resulted in a 30% CR rate and was relatively well tolerated (Roboz et al, 2008). Voreloxin, a novel topoisomerase II inhibitor, is completing early phase trials and may be synergistic in combination with cytarabine (Scatena et al, 2010). Finally, the plant-derived compound parthenolide, which inhibits NF-kB and specifically targets AML stem and progenitor cells (Guzman et al, 2007), is a promising compound.…”
Section: Other Treatments and Trials In Progressmentioning
confidence: 99%
“…Arsenic trioxide combined with LDAC in elderly patients with AML resulted in a 30% CR rate and was relatively well tolerated (Roboz et al, 2008). Voreloxin, a novel topoisomerase II inhibitor, is completing early phase trials and may be synergistic in combination with cytarabine (Scatena et al, 2010). Finally, the plant-derived compound parthenolide, which inhibits NF-kB and specifically targets AML stem and progenitor cells (Guzman et al, 2007), is a promising compound.…”
Section: Other Treatments and Trials In Progressmentioning
confidence: 99%
“…Maximum concentration in the cerebrum was 0.744 µgeq/g or 1.85 µMeq/g and in the cerebellum was 0.811 µgeq/g or 2.02 µMeq/g. Although brain tissues (cerebrum and cerebellum) showed tissue:plasma ratios ≤ 1.5, radioactivity in the brain achieved concentrations associated with anticancer activity in vitro [32,39]. These data suggested that active levels of vosaroxin may be achieved in the brain clinically where dose levels similar to or higher than 60 mg/m 2 have been investigated [37,49,50].…”
Section: Distribution Of Vosaroxin To Brain In Micementioning
confidence: 80%
“…It has www.impactjournals.com/oncotarget been shown to be active against various preclinical models and demonstrated synergistic activity in combination with other antineoplastic agents [29][30][31][32][33][34][35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies have demonstrated effective synergy when vosaroxin was combined with cytarabine (Ara-C) [48,51]. Authors suggested this enhanced cytotoxicity is likely the result of cells exiting S phase with cytarabine-induced DNA damage and entering G2 phase, unable to repair these DNA DSB and sustaining further insult as a result of the action of vosaroxin.…”
Section: Drug Evaluationmentioning
confidence: 99%